Peningkatan Motivasi dan Hasil Belajar Melalui Model Problem Based Learning - Hariyanti, Tutik (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
The purpose of this study was to increase motivation and learning outcomes of fourd grade Indonesian at elementary school Negeri 1 Nangsri. This research is a classroom action research. The research subjects were the third grade students, totaling 25 students. Data collection uses documentation, observation, questionnaire and test techniques. The validity of the data using source triangulation techniques and method triangulation. Data analysis was carried out descriptively, both qualitatively and quantitatively. The results of the study are as follows: (1) The learning motivation of students who are categorized as "high" in the first cycle is 64% or 16 students. In the second cycle to 92% or 23 students. 2) Student learning outcomes before the action only reached 32% or 8 students who completed.